2002
DOI: 10.1128/aem.68.11.5641-5646.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cytotoxin-Hemolysin mRNA in Nonculturable Populations of Environmental and Clinical Vibrio vulnificus Strains in Artificial Seawater

Abstract: The objective of this study was to develop a molecular detection method that better estimates the potential risk associated with the presence of Vibrio vulnificus. For that purpose, we applied seminested reverse transcription-PCR (RT-PCR) to viable but nonculturable (VBNC) populations of V. vulnificus and targeted the cytotoxin-hemolysin virulence gene vvhA. Three strains, two environmental, IF Vv10 and IF Vv18, and one clinical, C7184, were used in this study. Artificial seawater, inoculated with mid-log-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
6
35
0
Order By: Relevance
“…It seems difficult to know if such pathogenic effects were due to VBNC cells or to cells that reverted to a culturable state. But, recently, Fischer-Le Saux et al [19] detected a cytotoxin-hemolysin mRNA produced by a non culturable population of Vibrio vulnificus. They concluded that special attention should be given to the presence of potentially pathogenic VBNC cells in environmental samples when assessing public health risk.…”
Section: Discussionmentioning
confidence: 99%
“…It seems difficult to know if such pathogenic effects were due to VBNC cells or to cells that reverted to a culturable state. But, recently, Fischer-Le Saux et al [19] detected a cytotoxin-hemolysin mRNA produced by a non culturable population of Vibrio vulnificus. They concluded that special attention should be given to the presence of potentially pathogenic VBNC cells in environmental samples when assessing public health risk.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that vibrio species are pathogenic for humans, causing intestinal and extra-intestinal infections (21)(22)(23). Therefore, their detection as environmental contaminants is of a paramount importance for the control of both water quality and disease transmission (24,25). It has been shown that vibrio uses survival strategies such as that of entering into a VBNC state in response to unfavorable environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR product obtained with each set of primers for the DNA from strain Vp5 of V. parahaemolyticus was purified using a column system (QIAquick PCR purification kit) according to the recommendations of the manufacturer (QIAGEN). The nucleotide sequence of the purified PCR product was determined as previously described (9).…”
Section: Methodsmentioning
confidence: 99%